S-Ketamine Mediates Its Acute and Sustained Antidepressant-Like Activity through a 5-HT1B Receptor Dependent Mechanism in a Genetic Rat Model of Depression - du Jardin, Kristian G.; Liebenberg, Nico; Cajina, Manuel; Müller, Heidi K.; Elfving, Betina; Sanchez, Connie; Wegener, Gregers (Frontiers in Pharmacology, 2018)
Rationale: The mechanisms responsible for the unique antidepressant properties of ketamine have only been partly resolved. Recent preclinical reports implicate the neurotransmitter serotonin (5-hydroxytryptamine; 5-HT) in the antidepressant-like response of ketamine, and modulation of 5-HT1B receptors has been hypothesized to attain an important role. Objectives: To evaluate the role of endogenous stimulation of postsynaptic 5-HT1B heteroreceptors in the antidepressant-like activity of S-ketamine. Method: Flinders Sensitive Line (FSL) rats, a genetic model of depression, were depleted of endogenous 5-HT by 4-chloro-DL-phenylalanine methyl ester HCl administration (pCPA; 86 mg/kg/day for 3 days). In pCPA-pretreated and control FSL rats, the acute and sustained effects of a single dose of S-ketamine (15 mg/kg) and the selective 5-HT1B receptor agonist CP94253 (1-6 mg/kg) alone and in combination with S-ketamine were studied in the forced swim test (FST), a commonly used assay that detects antidepressant activity. Results: pCPA pretreatment decreased cortical 5-HT levels to ~6 % but did not affect the baseline behavioral phenotype of FSL rats. S-ketamine demonstrated acute and sustained antidepressant-like activity, both of which were abolished by 5-HT depletion. Combining S-ketamine with a sub-effective dose of CP94253 (1 mg/kg) rescued S-ketamine’s acute and sustained antidepressant-like effects, when CP94253 was administered 2 hr prior to the FST. Co-administration of S-ketamine and CP94253 did not affect the plasma level of either compound, suggesting that the observed behavioral interaction could not be ascribed to a kinetic drug-drug interaction. Conclusions:5-HT1B receptor activation during testing appears to be critical for S-ketamine’s antidepressant-like potentials in this model.